Tribological research of the tribological pairs under vacuum conditions - Bronček, J.; Dzimko, M.; Winkelmann, U.; Takeichi, Y. (Problems of Tribology, 2014)
The results of “ball on disc” tests to examine the friction coefficient under the specific conditions of low and high vacuum are presented. Nanocomposite coating CROMVIc2 (CrN/DLC2) was deposited by plasma assisted chemical vapor deposition PACVD on stainless steel AISI 304 (STN 41 7241) plates. Friction pairs - DLC coating surface and WC ball examined under low vacuum reached during the tribological tests significant lower friction coefficient values than those worked under atmospheric conditions.